Active labor market programs for the integration of youths and immigrants into the labor market : the Nordic experience - Nekby, Lena (UN ECLAC SantiagoCL, 2008)
Surveys the evaluation literature on active labour market programmes (ALMPs) in the Nordic labour market in order to provide a general overview of the success and failure of different types of ALMPs as well as a more detailed account of the Nordic experience with targetted programmes towards vulnerable groups such as unemployed youth and immigrants.